2023
DOI: 10.1186/s40779-023-00452-0
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the heart: from molecular mechanisms to clinical therapeutics

Abstract: Heart injury such as myocardial infarction leads to cardiomyocyte loss, fibrotic tissue deposition, and scar formation. These changes reduce cardiac contractility, resulting in heart failure, which causes a huge public health burden. Military personnel, compared with civilians, is exposed to more stress, a risk factor for heart diseases, making cardiovascular health management and treatment innovation an important topic for military medicine. So far, medical intervention can slow down cardiovascular disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 209 publications
0
8
0
Order By: Relevance
“…Adult human cardiomyocytes are terminally differentiated and have virtually no regenerative capacity, making it difficult to restart cardiomyocyte proliferation. However, some pathways implicated in the reactivation of the cellular cycle of cardiomyocytes have been identified: Hippo-Yap is involved in the proliferation, migration, and apoptosis of cardiomyocytes, in fact, it has been observed that its deficiency improves the regeneration of cardiomyocytes in adult mice; Notch is an important pathway in cardiac generation in zebrafish, and it regulates the maturation of the endocardium and promotes the proliferation of cardiomyocytes; Nrg1 induces cell cycle re-entry and cardiomyocyte division in adult mice [ 35 ]. The regeneration of cardiomyocytes has also been observed in humans [ 36 ], but as this is insufficient to restore the contractile function of the damaged heart, it is therefore important for patients to implement regenerative therapies.…”
Section: Cardiac Repair and Regenerationmentioning
confidence: 99%
“…Adult human cardiomyocytes are terminally differentiated and have virtually no regenerative capacity, making it difficult to restart cardiomyocyte proliferation. However, some pathways implicated in the reactivation of the cellular cycle of cardiomyocytes have been identified: Hippo-Yap is involved in the proliferation, migration, and apoptosis of cardiomyocytes, in fact, it has been observed that its deficiency improves the regeneration of cardiomyocytes in adult mice; Notch is an important pathway in cardiac generation in zebrafish, and it regulates the maturation of the endocardium and promotes the proliferation of cardiomyocytes; Nrg1 induces cell cycle re-entry and cardiomyocyte division in adult mice [ 35 ]. The regeneration of cardiomyocytes has also been observed in humans [ 36 ], but as this is insufficient to restore the contractile function of the damaged heart, it is therefore important for patients to implement regenerative therapies.…”
Section: Cardiac Repair and Regenerationmentioning
confidence: 99%
“…A multitude of different multipotent stem cell populations have been utilized in a multitude of different animal studies and clinical trials, including BM-derived populations, MSCs derived from various locations, as well as CSC/CPC. Results have been variable, although in cases of successful studies, the main effects have been improvements in local perfusion and capillary density, myocardial tissue viability and cardiac function, as well as infarct size [ 141 ]. This secretory function may be augmented through forced overexpression of certain genes, including Igf-1 , Akt and stromal derived growth factor-1 ( Sdf-1 ); when overexpressed, these may further facilitate the local function of these stem cell therapies or aid in recruitment of local stem and progenitor cells, further aiding in cardiomyocyte survival, angiogenesis, and overall improvement in cardiac function.…”
Section: Stem and Progenitor Cell Therapies For Ischemic Heart Diseas...mentioning
confidence: 99%
“…One key method is the promotion of cardiomyocyte growth, which replaces the injured cardiomyocytes. Numerous signaling events, such as chromatin accessibility and mitogenic signals, regulate this process [ 44 , 45 ]. Neovascularization and lymphangiogenesis are very important for heart regeneration because they help set up working blood and lymphatic vascular networks in the damaged areas [ 46 ].…”
Section: Reviewmentioning
confidence: 99%